Pengaruh Substitusi Pati Ganyong (Canna edulis Kerr) terhadap Sifat Fisik, Kimia dan Sensoris Roti Bagelen - Kornelius Jaka; Dyah Ilminingtyas Wahyu Handayani; Ni Komang Ayu Artiningsih (Universitas 17 Agustus 1945 Semarang, 2024)
Bagelen bread is a processed dry bread product, processed by re-baking the finished bread to become dry bread. This study aims to determine the right formulation of canna starch substitution for wheat flour in making bagelen dry bread, and to examine the effect of canna starch substitution on the physical properties, chemical properties and sensory properties of bagelen. The study was conducted at the Laboratory of Food and Agricultural Product Processing, Faculty of Agricultural Technology, University of 17 August 1945 Semarang. The research design used a completely randomized design (CRD) with 4 treatments and each treatment was repeated 3 times. Data were analyzed using Anova (Analysis of Variance) at a 95% confidence level. If significantly different, Duncan's Multiple Range Test (DMRT) will be carried out. The results of the analysis of physical hardness properties showed significant differences and the results of the color analysis (L a * b *) showed no significant differences. The results of the chemical properties analysis showed that there was no significant difference in water, ash and fat content, but there was a significant difference in protein and carbohydrate content in bagelen bread. The protein content of bagelen bread will decrease in line with the increasing portion of ganyong starch. Meanwhile, carbohydrate levels will increase as the number of canna starch substitutes increases. The results of the sensory properties analysis of color, aroma, taste and texture of bagelen bread showed significant differences. Substitution of canna starch up to 40% did not affect the level of preference for the attributes of taste, color, and aroma of bagelen bread, but the texture of the substitution with canna starch was less preferred.